How do the models to measure bubbles in the stock market - Ding, Yun (2007)
Bubble economy is a phenomenon frequently occurs in the process of finance opening and an essential factor contributing to financial crisis. Once bubbles burst, financial crisis is quite possible. Stock market bubble is a key component of a countrys economic bubble, thus it is important to analyze the developing process of stock market bubble and to find out the method to eliminate harmful bubble component.